Raman Spectroscopic Analysis of a Mid-19th Century Reredos by Sir George Gilbert Scott - Christopher Brooke; Howell Edwards; Peter Vandenabeele; Sylvia Lycke; Michelle Pepper (Heritage, 2023)
A painted stone reredos in the Priory Church of St Cuthbert, Worksop, Nottinghamshire, UK, was analysed before recent conservation to determine the pigment scheme employed. The screen was created by the eminent British architect Sir George Gilbert Scott in the middle decade of the 19th Century. The results help inform the wider range of palettes employed by British architects and craftspeople working in the 19th and early 20th centuries which have previously been little studied. The pigments generally were high-quality vermilion (red), chrome yellow (yellow), and ultramarine (blue), and several alternatives were also evident such as red lead and haematite for red, bone black, and carbon black for black. Lightening and darkening agents were incorporated as lead white, barytes, and carbon, and pigment mixtures were used to achieve the colours dark blue-red, and green.